Pengaruh Pelatihan terhadap Kinerja Tenaga Kerja Kontruksi (Sertifikasi) pada Bidang Bina Kontruksi dan Pengendalian Dinas PUPR Provinsi Jambi - Okta Verdino (Universitas Batanghari Jambi, 2019)
The Effect of Training on the Performance of Construction Workers in the Field of Construction and Control of the PUPR Office of Jambi Province, explained from the results of a simple linear regression equation calculation. The simple linear regression equation obtained is as follows Y = 6,519 + 0,801. This equation shows that the training regression coefficient has a tight direction toward the performance of construction workers in the construction sector and the control of the Jambi provincial PUPR office.The Correlation Coefficient of the value r = 0.515 means that training has a close relationship with Performance (Y) in the Field of Construction and Control of the PUPR Office of Jambi Province, which is equal to 51.5%.The Determination Coefficient is known from the value of r² = 0.511 (51.1%) which means that the contribution of variable X (training) to variable Y (performance) is 51.1%, the rest (100% - 51.5% = 0.485) Influenced by other variables not examined in the study this. Keywords: Training ; Performance of Construction Workers